Applications of magnetic nanoparticles for boundarics in biomedicine - Fang Yang; Juan Li; Tianxiang Chen; Wenzhi Ren; Changyong Gao; Jie Lin; Chen Xu; Xuehua Ma; Jie Xing; Hongying Bao; Bo Jiang; Lingchao Xiang; et al. (Fundamental Research)
Accurate mapping of boundarics in biomedicine is crucial for improving early diagnosis, crafting individualized medical regimens, and evaluating therapeutic efficacy. Magnetic nanomaterials have attracted considerable attention in the diagnosis and treatment of disease lesions, due to their unique physicochemical properties (e.g., magnetically responsive performance and superparamagnetism). In recent years, the application of magnetic nanoparticles in disease imaging has advanced rapidly, showing significant advantages in the detection of tumors and other major diseases. Leveraging their strong magnetic properties, magnetic nanoparticles not only enable high-precision real-time detection of lesions but also possess potential for long-term monitoring. In this article, key aspects of magnetic nanomaterials applied for boundarics in biomedicine are discussed, including controllable material preparation, material performance optimization, and lesion boundary imaging. Furthermore, the prevailing strategies for magnetic nanomaterials and their successful implementation in multimodal imaging techniques are summarized, with particular emphasis on their significance in defining the boundaries of tumors and other major diseases. Ultimately, the challenges that persist in boundarics in biomedicine and the corresponding approaches are presented, providing insights to advance boundary imaging techniques.